Takhrij Study and Understanding of Hadith on The Main Basis of Implementing The Sadakah Basorakan Tradition - Saputra, Edriagus; Zakiyah, Zakiyah; Gustianda, Nana; Putra, Alven; Eramahi, Eka (Al-Fikru: Jurnal Ilmiah, 2023)
This research aims to determine the quality of the hadith and the understanding of the Ulama which is the main foundation for the people of Jorong Lubuk Alung, Agam Regency, to carry out the sadakah basorakan tradition which is considered an act of ridicule for other communities. This study uses the library research method of hadith which is the main foundation of the sadakah basorakan tradition. Primary data sources, namely the book mu'jam Al-Mufahras li Al-Hadith, Tis'ah pole, book of rijalul hadith and books of syarah hadith. While the secondary sources are books, related journal articles. The results of the study show that the hadith which is the basis for the community in carrying out the sadakah basorakan tradition has a dhaif status, because there is a hadith sanad who has been harassed by the scholars. But the Nasa'i priest considers this hadith to be a hasan lighairihi hadith, even though this hadith has the status of dhaif and there are no other hadiths that support it to rise to the status of hasan lighairihi hadith, this hadith does not conflict with other hadiths, the verses of the Qur'an or ijma' scholars. In terms of the understanding of scholars, this hadith can be practiced as a motivation in worship, especially in alms giving for the people of Jorong Lubuk Alung, Agam Regency.